2021
DOI: 10.1186/s12883-021-02251-3
|View full text |Cite
|
Sign up to set email alerts
|

Wall shear stress gradient is independently associated with middle cerebral artery aneurysm development: a case-control CFD patient-specific study based on 77 patients

Abstract: Background Previously published computational fluid dynamics (CFD) studies regarding intracranial aneurysm (IA) formation present conflicting results. Our study analysed the involvement of the combination of high wall shear stress (WSS) and a positive WSS gradient (WSSG) in IA formation. Methods We designed a case-control study with a selection of 38 patients with an unruptured middle cerebral artery (MCA) aneurysm and 39 non-aneurysmal controls to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Few studies have been conducted on VBD with BA‐dissecting aneurysms. It is unclear whether the formation of dissecting aneurysms is related to pathological changes in the vessel wall and wall shear stress in patients with VBD [ 2 , 19 , 20 , 21 ]. This needs to be further explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been conducted on VBD with BA‐dissecting aneurysms. It is unclear whether the formation of dissecting aneurysms is related to pathological changes in the vessel wall and wall shear stress in patients with VBD [ 2 , 19 , 20 , 21 ]. This needs to be further explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current view on the aetiology of IA, the haemodynamic factor, that is, mainly the magnitude of WSS and its gradient, plays a key role in the formation of aneurysms [10,23]. The results of liquid flow in glass model studies and CFD studies have shown that the geometry of the bifurcation, including the diameter of the vessels forming the bifurcation and the bifurcation angle, plays an important role in the distribution of WSS and turbulence on the bifurcation components [12,13,21,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…According to the current view on the aetiology of IAs, the haemodynamic factor, that is, mainly the magnitude of WSS and its gradient, plays a key role in the formation of aneurysms (10,23).…”
Section: Discussionmentioning
confidence: 99%